Changes from COVID-19. A perspective from internal pediatric medicine - Pedro J. Alcalá Minagorre; Enrique Villalobos Pinto; José Miguel Ramos Fernández; Rosa Rodríguez-Fernández; Miguel Vázquez Ronco; Luis Escosa-García; Juan Ignacio Montiano Jorge; Juan José García García (Elsevier, 2020)
The SARS-CoV2 pandemic dimension has affected the Hospital Pediatrics Medicine assistance in our country. New challenges generated by COVID-19 require a series of proactive measures, based on existing scientific knowledge and standards of good practice, that allow the Pediatric Hospital services readiness and operability. Hospital Internal Pediatrics, as responsible of integral care of the hospitalized child, plays a leading role in the new hospital model emerging from this crisis. This review analyzes the impact of the current SARS-CoV2 epidemic on pediatric care, and perspective of new COVID-19 outbreaks in coexistence with other viral infections. Changes secondary to pandemic involved in Hospital pediatric units must be analyzed, and how to prepare for future epidemics, also the involvement of pediatric units in adult care and the possible opportunities for improvement. Assistance of patients with chronic complex conditions in epidemic circumstances, safety aspects, opportunities for teaching and ethical considerations are reviewed. The Spanish Society of Hospital Pediatrics Medicine offers with this article a series of resources for Internal pediatric Medicine practitioners responsible to face next challenges in pediatric hospitalization units. Resumen: La dimensión de la pandemia por SARS-CoV2 ha afectado a la organización asistencial de la Pediatría Hospitalaria de nuestro país. Los nuevos retos generados por la COVID-19 exigen una serie de medidas proactivas basadas en los conocimientos científicos existentes y las normas de buena práctica, que permitan la preparación y la mayor operatividad de los servicios pediátricos hospitalarios. La Pediatría Interna Hospitalaria, como responsable de la atención integral del niño hospitalizado, tiene un papel principal en el nuevo modelo de hospital surgido de esta epidemia. En la presente revisión se analiza la repercusión pediátrica que ha tenido la epidemia por SARS-CoV2 y la preparación ante futuros rebrotes, en posible coexistencia con otras infecciones virales. Se revisa también la implicación de las unidades pediátricas en la asistencia de adultos y la atención de pacientes crónicos complejos y se ofrecen recomendaciones sobre aspectos de seguridad, consideraciones éticas y docencia de los futuros pediatras durante la crisis. La Sociedad Española de Pediatría Hospitalaria (SEPHO) pretende con este documento ofrecer a los pediatras internistas hospitalarios una serie de reflexiones y recursos de utilidad en un escenario con muchas incertidumbres.